2022
DOI: 10.18502/jmehm.v14i21.8181
|View full text |Cite
|
Sign up to set email alerts
|

The role of narrative medicine program in promoting professional ethics: perceptions of Iranian medical students

Abstract: Narrative medicine (NM) is an educational tool that can be used to promote the professional competencies of medical students. This study aimed to investigate Iranian medical students’ perceptions of the first NM program offered in 2019. The study was conducted on 69 medical interns who participated in the weekly NM program that was part of the professional ethics course for two months. We used a questionnaire to determine medical interns' perceptions and personal attitudes toward NM. Three experts confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This interdisciplinary approach promotes introspection, adaptability, and a better understanding of patient encounters, in accordance with the broader objectives of medical education (Phelan, 2022). Furthermore, Daryazadeh et al (2022) demonstrated that narrative medicine education enhances medical students' professional competencies, fostering empathy and reflection skills, which aligns with the overarching objectives of medical education to cultivate well-rounded and ethical healthcare professionals.…”
Section: Objectives In Narrative Medicine Educationmentioning
confidence: 74%
“…This interdisciplinary approach promotes introspection, adaptability, and a better understanding of patient encounters, in accordance with the broader objectives of medical education (Phelan, 2022). Furthermore, Daryazadeh et al (2022) demonstrated that narrative medicine education enhances medical students' professional competencies, fostering empathy and reflection skills, which aligns with the overarching objectives of medical education to cultivate well-rounded and ethical healthcare professionals.…”
Section: Objectives In Narrative Medicine Educationmentioning
confidence: 74%
“…• Enhanced learning of empathy [111,125,127,128,135,138,145,149,150,[152][153][154][155][156][157][158][159][160][161][162][163][164][165][166] • Improved ability to understand, interpret, and engage with others [11,19,111,114,135,155,[167][168][169][170][171][172][173] • Enhanced patient-centred care [111] • Enhanced building of cultural sensitivity and contextual considerations [114,124,130,136,140,143,170,[173][174][175][176]…”
Section: Patient Benefits Clinician Benefitsmentioning
confidence: 99%
“…• Enhanced meaning making [11, 19, 22, 24-29, 173, 180, 182, 265-268] • Enhanced self-reflection [116,135,139,158,[269][270][271][272] • Enhanced professional identity formation [139,152,157,202,241,247,[273][274][275] Enhanced development of professional common culture [139,276] through:…”
Section: Patient Benefits Clinician Benefitsmentioning
confidence: 99%
“…Rita Charon states, "by rendering whole that which they observe and undergo, doctor-writers can reveal transcendent truths, exposed in the course of illness, about ordinary human life" and develop "deep and therapeutically consequential understandings of the persons who bear symptoms are made possible in the course of hearing the narratives told of illness" [7]. Evidence is strong that narrative curricula foster empathetic concern among health professions students [17][18][19][20][21] by allowing students to develop core skills necessary for empathy, including perspective-taking, valuing others, and humanizing patients [22]. Thus, narrative practice can lead to meaningful gains in professional development by giving students the space to consciously process the gap between the technical knowledge learned in medical school and the tacit knowledge learned through patient interactions and stories [23].…”
Section: Introductionmentioning
confidence: 99%